2001
DOI: 10.1002/pd.179
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive information about Down syndrome: a content analysis of serum screening leaflets

Abstract: It is recommended practice that prior to prenatal screening, women receive information about the condition(s) being tested for. The present study critically evaluated information about Down syndrome as contained in 80 leaflets provided to pregnant women in the UK prior to serum screening. First, a content analysis by information type was conducted to give an overall picture of the material provided. Second, the image of the condition as conveyed by the content was analysed and compared with a similar study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…The classification used in the current study was based on the criteria used in earlier studies which described written information about the condition for which screening was being conducted in prenatal screening leaflets. 3,7 Examples of positive information were: 'some people with Down's syndrome enjoy good health' and 'most people with Down's syndrome live to be over 50 years of age, some live to be over 70'. Examples of negative information were: 'severe mental handicap (IQo50) will result in most cases' and 'Down's syndrome is the single most common cause of mental disorder'.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The classification used in the current study was based on the criteria used in earlier studies which described written information about the condition for which screening was being conducted in prenatal screening leaflets. 3,7 Examples of positive information were: 'some people with Down's syndrome enjoy good health' and 'most people with Down's syndrome live to be over 50 years of age, some live to be over 70'. Examples of negative information were: 'severe mental handicap (IQo50) will result in most cases' and 'Down's syndrome is the single most common cause of mental disorder'.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Bryant et al 3 described written information women were given about Down's syndrome. About a fifth of the 80 leaflets analysed gave no information about the condition at all.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…121 Secondly, few would disagree with Alderson 122 that those undergoing screening need`realistic, unprejudiced knowledge about people with Down's syndrome.' * First, the offer of a test for a condition may be perceived as a recommendation that something i.e.…”
Section: Impact Of the Abnormality: Where Does The Information Come Fmentioning
confidence: 99%
“…Material contained in prenatal screening information leaflets has also been subject to criticism 5 . One study evaluating 80 leaflets provided in the UK to pregnant women prior to serum screening found that one‐third contained no descriptive information about Down’s syndrome 6 . In the remaining two‐thirds, information about the condition was overwhelmingly medico‐clinical in nature.…”
Section: Introductionmentioning
confidence: 99%